Application of Silicon Nitride (Si3N4) Ceramics in Ball Bearing - Wijianto, Wijianto (Universitas Muhammadiyah Surakarta, 2014)
This paper is discus about silicon nitride ceramics in application to ball bearing. Silicon nitride (Si3N4) have advance properties such as consistent at temperatureoperation up to 1000Â°C, greater thermal shock resistance, lower density and low thermal expansion. This properties gives some benefit for ball bearing material such as higher running speed, reduce vibration of the shaft, will improve the life time and maintenance cost, lower heat generated, less energy consumption, lower wear rate, reducing noise level and reduce of using lubricant.The sintering methods are used to produce ball bearing from silicon nitride. Some techniques can be applied to increase ceramics strength which are reduce porosity, reduce grain size, reduce surface flaw and proof stressing.The surface finishing of the ceramic bearing is very important because silicon nitride as a brittle material, its strength is limited to the flaw sizes especially the flaw at the surface.